Basic research on required specifications for water-soluble gas mining casing pipes (J) (GPI Journal, 2023)
For FRP casing pipes required for extracting water-soluble natural gas, GPI standard semi-flush coupling E20 to E40 standards apply from a depth of about 1500 m, just like hot spring pipes. Since the pumped water contains a large amount of fine sandy gravel, a pipe with a stainless steel net screen installed on the top of a 3% open area slit is used with a space on the outside. The water-soluble gas-containing layer may be subject to soil contact friction due to unexpected partial cave-ins at the underground floor during construction of pipe elevators. In this research, we ensured that the casing tube had the necessary axial pushing force (compressive force) (the allowable compressive strength in the axial direction of the GPI semi-flush coupling was equal to or higher than the allowable buckling force of the pipe end face, which is the discontinuous fiber of the pipe body). In addition to what was considered necessary and sufficient according to the quality standards (quality standards), it was also found that a pull-out force with the same allowable strength, which was indispensable for countermeasures against partial cave-ins that had not been anticipated, was also necessary to improve efficiency during construction. As a result, for construction that requires tensile reinforcement, it is effective to strengthen the axial tension coupling by additionally using an inner coupling, which is effective, and to use equipment that has a casing pipe rotation pull-out f